Enhancing electrochemical performance by control of transport properties in buffer layers – solid oxide fuel/electrolyser cells1. Issue 17 (7th May 2015) - Ramasamy, Devaraj; Nasani, Narendar; Brandão, Ana D.; Pérez Coll, Domingo; Fagg, Duncan P.
<x xml:space="preserve">Abstract</x> Extension of electrocatalytically active sites for oxygen electrode reaction by the presence of a mixed conducting buffer layer.